2002
DOI: 10.1097/00006231-200206000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of nuclear medicine imaging for the detection of occult gastrointestinal haemorrhage

Abstract: Acute gastrointestinal bleeding is often intermittent and the bleeding source may be difficult to locate, resulting in delay of potentially life-saving treatment. The aim of this study was to determine the clinical utility of 99mTc labelled red blood cell imaging and [99mTc]pertechnetate (Meckel's scan) imaging in a series of 137 patients admitted over a 5 year period to hospital for management of acute gastrointestinal bleeding. Of the 137 patients, 70 had positive 99mTc red blood cell studies. Eleven of 24 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 6 publications
0
32
0
3
Order By: Relevance
“…Gunderman et al had an overall positive scintigraphic screening in 46% of the 249 patients undergoing 99mTc-RBC scans over a 10-year study period [30]. Similar positive scintigraphic screening rates ranging from 46-73% have been confirmed [31,[66][67][68]. Jacobson and Cerqueira showed that upper sources of bleeding in the stomach or small bowel were more common when the nuclear screening studies became positive on delayed imaging [31].…”
Section: Intermittent Gi Bleed/empiric Embolizationmentioning
confidence: 93%
“…Gunderman et al had an overall positive scintigraphic screening in 46% of the 249 patients undergoing 99mTc-RBC scans over a 10-year study period [30]. Similar positive scintigraphic screening rates ranging from 46-73% have been confirmed [31,[66][67][68]. Jacobson and Cerqueira showed that upper sources of bleeding in the stomach or small bowel were more common when the nuclear screening studies became positive on delayed imaging [31].…”
Section: Intermittent Gi Bleed/empiric Embolizationmentioning
confidence: 93%
“…First, the ability to localize the source of bleeding with radionuclide scanning, especially in the foregut, has been repeatedly demonstrated to be poor; even a positive scan does not allow determination of the cause of the bleeding. In addition, because nuclear scanning is not therapeutic, a follow-up study, such as catheter-directed angiography or endoscopic examination, must be subsequently performed (24).…”
Section: Identification Of the Bleeding Cause-criteriamentioning
confidence: 99%
“…2 5 Angiography is rarely helpful unless the patient is actively bleeding at a rate of more than 3-5 ml/min 2 5 12 and scintigraphy with technetium labelled red cells is of limited value, particularly in the foregut. 13 Meckel scans are helpful when positive, but if negative do not exclude a Meckel's diverticulum as a bleeding source.…”
mentioning
confidence: 99%